PENGARUH PEMAHAMAN PERPAJAKAN TERHADAP PRESTASI AKADEMIK MAHASISWA: MOTIVASI DAN KUALITAS PEMBELAJARAN DOSEN SEBAGAI MODERASI - Fadjar Harimurti; Bambang Widarno (Riset Manajemen dan Akuntansi, 2020)
This study aims to analyze the role of motivation and learning quality of lecturer as the moderating in the effect of understanding taxation on student academic achievement of accounting students at the Faculty of Economics, UNISRI Surakarta. This study using quantitative descriptive methods. The population is all students of the faculty of economics, accounting study program UNISRI Surakarta. Sampling using a purposive sampling technique. Sample criteria are students who are active until the academic year 2019/2020 and have taken Tax Accounting I and II courses. Data analysis techniques using multiple linear regression analysis and absolute residual test. The results showed that (1) understanding taxation, motivation, and learning quality of lecturer significantly effect on student academic achievement; (2) motivation is a moderating variable that can strengthen the effect of understanding taxation on student academic achievement; (3) learning quality of lecturer is a moderating variable that can strengthen the effect of taxation understanding on student academic achievement.